Effects of 8-Week Core Exercises on Free Style Swimming Performance of Female Swimmers Aged 9-12 - GENCER, Yıldırım Gökhan (Asian Journal of Education and Training, 2018)
With this study, it is aimed to review the effects of 8-week core exercises, which are scheduled before the routine exercises, on changes over certain physical and motoric attributes and freestyle swimming performance of female athletes of the youngest age group, which is 9-12. For the study, a group of 12 female licensed swimmers who had a swimming background of 3 years in city of Van is chosen to be core exercise group (CEG) and set as experimental group. And 12 female swimmers are chosen to be in control group. The athletes are scheduled to perform regular swimming exercises for competition, five days a week and for approximately 90 minutes per day. In addition to control group, CEG is scheduled to perform 20 minutes of low intensity, fixed duration and repetitive core exercises before every routine exercise for 8 weeks. Chosen measurements are obtained from the athletes both at the beginning and after 8 weeks and the change between pretest and posttest values is evaluated. For the statistical data analysis, non-parametric tests of Wilcoxon and Mann Whitney U tests are used. As a results of the study, the group of swimmers aged 9-12 who underwent 8 weeks of low intensity core exercises showed differences compared to pretest and posttest values of control group, even though not statistically significant (p>0,05). As a result, compared to the control group, a 1-2 seconds of decrease – especially when it is a very important amount for this sport – in 25 m and 50 m free style swimming ranks is attributed to the effect of core exercises, and it is reckoned that low intensity core exercises may positively affect the free style swimming performance of female swimmers aged 9-12.